Healing the individual, family and communities after the war - Ajduković, Dean (Array, 2000)
The consequences of massive traumatization were analyzed using the recent experiences from the wars that accompanied the breakup of former Yugoslav federation. The emphasis was on illustrating how the destruction of communities and individuals is linked to manipulation and creation of powerlessness. The ethnical cleansing and war-rape were carefully designed to create terror among the civilians and create millions of refugees. Refugees experiences and the psychosocial consequences of uprooting were discussed in the context of massive traumatization, increasingly negative psychological consequences of prolonged displacement and the learned helplessness model. The people need to integrate and work through the painful collective experiences, so that they can turn toward the future. This is also the only way the cycle of violence and victimization can be interrupted. Some of the interventions need less sophisticated skills, but can typically serve many clients. Other interventions require higher levels of expertise, but fortunately are required by a more limited number of clients. Thus, a range of psychosocial interventions need to be put in place in order to meet the needs of recovering individuals, families and communities. This thinking is illustrated by the "Pyramid of psychosocial interventions in a community". Trauma recovery and social reconstruction processes after war both deal with disempowered people and communities that are also psychologically disconnected from others. Therefore, the empowering assistance is a part of the rebuilding relationships. It needs to recreate initiative, autonomy, competence, tolerance, identity and trust that have been damaged by violence. If these issues are not addressed but swept under the carpet, the pain, fear, anger and indignation will not be dealt with and as such will remain a threat for outbreak of future violence.